Tamm–Horsfall glycoprotein engages human Siglec‐9 to modulate neutrophil activation in the urinary tract. Issue 10 (22nd August 2017) - Patras, Kathryn A; Coady, Alison; Olson, Joshua; Ali, Syed Raza; RamachandraRao, Satish P; Kumar, Satish; Varki, Ajit; Nizet, Victor
Abstract : Urinary tract infections are a major problem in human medicine for which better understanding of native immune defenses may reveal new pathways for therapeutic intervention. Tamm–Horsfall glycoprotein (THP), the most abundant urinary protein, interacts with bacteria including uropathogenic Escherichia coli (UPEC) as well host immune cells. In addition to its well‐studied functions to antagonize bacterial colonization, we hypothesize that THP serves a critical host defense function through innate immune modulation. Using isolated human neutrophils, we found that THP binds neutrophils and that this interaction reduces reactive oxygen species generation, chemotaxis and killing of UPEC. We discovered that THP engages the inhibitory neutrophil receptor sialic acid‐binding Ig‐like lectin‐9 (Siglec‐9), and mouse functional ortholog Siglec‐E, in a manner dependent on sialic acid on its N‐glycan moieties. THP‐null mice have significantly more neutrophils present in the urine compared with wild‐type mice, both with and without the presence of inflammatory stimuli. These data support THP as an important negative regulator of neutrophil activation in the urinary tract, with dual functions to counteract bacterial colonization and suppress excessive inflammation within the urinary tract.